El impacto de las reformas tributarias en la capacidad financiera de las empresas jurídicas constructoras de Riobamba, período 2024 - Londo Shagñay, Elvis Ariel (2025)
The research examines how the 2024 tax reforms have affected the economic situation of construction companies in Riobamba. The situation is related to the reduction of VAT to 5% on certain construction materials, which has made it difficult for these entities to maintain their financial stability. The purpose is to recognize the relationship between recent tax regulations and financial capacity. To achieve this, a mixed-method approach was used, involving a survey and the examination of the financial statements of five companies selected for their tax compliance. Additionally, statistical methods such as the normality test (Shapiro-Wilk and Kolmogorov-Smirnov), Student’s T-test, and Pearson's correlation coefficient were used. The findings showed a 24.3% reduction in current liquidity and an 8.3% increase in the total tax burden. There was a 6.7% reduction in sales, along with a 20% increase in administrative expenses. The evaluation coefficient showed a significant relationship between the tax reform and the decrease in financial capacity, confirming the proposed hypothesis. The results obtained provide a better understanding of how recent tax reforms have impacted the financial situation of the construction sector in Riobamba. The research demonstrates the direct impact of the reforms on liquidity, profitability, and indebtedness, revealing the financial situation these companies face today.